Pengaruh Model Problem Solving Terhadap Hasil Belajar Siswa Kelas V Pelajaran IPAS - Nico Thomas Sitohang; Emelda Thesalonika; Aprido Bernando Simamora (Jurnal Ilmu Pendidikan dan Sosial, 2026)
This study aims to determine the effect of the Problem Solving model on the learning outcomes of Year 5 pupils at SD Negeri 091567 BAH JAMBI. The study was conducted in Year 5 at SD Negeri 091567 BAH JAMBI with a sample of 20 pupils, comprising 11 girls and 9 boys. Based on the results of the tests and data analysis carried out, calculations using the t-test yielded a t-value of 24.508, which was then compared with the critical t-value of 1.725, with df=39 and a significance level of 0.05. The difference is considered significant if ????ℎi???????????????? > ????????????????????????. If ????ℎi???????????????? > ????????????????????????, then ???????? is rejected and ???????? is accepted, and if ????ℎi???????????????? < ???????????????????????? then ???????? is accepted and ???????? is rejected. Based on the data obtained from the pre-test, the pupils achieved an average score of 56.20, which did not meet the minimum passing mark of 70; however, after being taught using the Problem Solving model, they achieved a post-test score of 85.60. This indicates that the Problem Solving model has an impact on the learning outcomes of Year 5 pupils at State Primary School 091567 BAH JAMBI.